'Chronic unease' for safety in senior managers: an interview study of its components, behaviours and consequences. Issue 5 (27th May 2016) - Fruhen, L.S.; Flin, R.
Abstract : The high reliability literature describes a sense of chronic unease as supporting managers' ability to deal with (safety) risks. This concept has been proposed to contain five components, namely the traits of propensity to worry, pessimism, and the cognitive abilities of requisite imagination, flexible thinking and vigilance. We study their applicability to senior managers' experience of chronic unease and explore related behaviours and consequences. Semi-structured interviews ( n  = 27) were conducted with senior managers from the energy sector. Content analysis identified flexible thinking most frequently, followed by pessimism, propensity to worry, vigilance and requisite imagination. Experience additionally emerged as a theme. Sections that had been coded as flexible thinking were frequently also coded as a behaviour, suggesting it to be a partially observable response to chronic unease. Other behaviours that emerged as related to chronic unease were demonstrating safety commitment, transformational and transactional leadership styles, and seeking information. Chronic unease was described as having positive effects on safety, positive and negative effects on team interaction and negative effects on business and the managers' personal outcomes. The findings indicate that the five components provide a basis for the measurement of chronic unease and suggest central behaviours and responses that should be considered in its future investigation.